2018
DOI: 10.1002/em.22170
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Carnicor, Venofer, and Sevelamer on the levels of genotoxic damage in end‐stage renal disease patients

Abstract: End-stage renal disease (ESRD) patients present high levels of phosphorus and calcium products in serum, which contribute to the development of vascular calcification and cardiovascular disease, and to low iron stores and carnitine deficiency. For these reasons, ESRD patients are generally supplemented with different medicines. Some of the most common treatments include the use of Carnicor, Venofer, and Sevelamer drugs. Carnicor is used as a source of L-carnitine, acting as antioxidant and neuroprotector. Veno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 60 publications
(100 reference statements)
0
1
0
Order By: Relevance
“…Previously, it has been found that the oxidative damage to DNA evaluated with the marker 8-OHdG in peripheral blood lymphocytes increased more in patients on chronic HD than in non-dialyzed patients ( 37 ). On the other hand, sevelamer hydrochloride has previously been reported to have the ability to reduce oxidative damage to genetic material ( 38 ). The authors of a recent study reported the potential effect of sevelamer treatment on inflammation and possible oxidative RNA modifications ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been found that the oxidative damage to DNA evaluated with the marker 8-OHdG in peripheral blood lymphocytes increased more in patients on chronic HD than in non-dialyzed patients ( 37 ). On the other hand, sevelamer hydrochloride has previously been reported to have the ability to reduce oxidative damage to genetic material ( 38 ). The authors of a recent study reported the potential effect of sevelamer treatment on inflammation and possible oxidative RNA modifications ( 39 ).…”
Section: Discussionmentioning
confidence: 99%